(untitled) (African Journal of Biomedical Research, 2019)
In 2014, as part of the Medical Education Partnership Initiative in Nigeria (MEPIN) project, a process of undergraduate mentored research for medical and dental undergraduates in the clinical phase of their training was commenced. The students already had a good foundation in their pre-clinical years in that they had been exposed to research methods and biostatistics during the period. Ordinarily, they were expected to undertake group research projects during some specific clinical rotations in the clinical years of their training, but this new initiative was designed to have students granted some protected time for individual mentored research during the period of clinical training. I commend the articles written by these students to you for reading. Many of them have brought out new knowledge that will enhance the health of the population if implemented. I also believe that this experience will make some of them choose careers that incorporate health research. This kind of mentored research should be available to all undergraduates who wish to enjoy such opportunities.